The Creation Of Furniture Products Design From Stem Waste Of Sugar Palm Tree (Arenga Pinnata) - I Wayan Seriyoga Parta; I Wayan Sudana; - Hasdiana (Institut Seni Indonesia Denpasar, 2017)
Sugar Palm tree (Arenga Pinnata) is one of potential natural resources that can be used as a based material of furniture products. But, this sugar palm tree potential hasnâ€™t exploited maximally and only throws away as a waste that contaminates the environment. On the other side, woods that have been used as based material of furniture products are getting rare and expensive. Based on that problem, this research is aimed to design new furniture products models that exploite the stem waste as a prominent based material.Â This research uses experiment method with steps: 1) finding and formulating concepts of furniture products design creation based on analysis towards the stem waste of sugar palm tree characteristics; 2) implementing of finding concepts to become furniture products models from stem waste of sugar palm tree. As a result of the research, it is found â€œtubeâ€ concept and tatah carved concept as a right concept to be applied in creation of furniture products from stem waste of sugar palm tree. Implementing of â€œtubeâ€ concept and tatah carved concept is made successfully in shape of some furniture products design such as:Â table model, chair model and wardrobe model. Realization of these designs has concerned with the use of sugar palm tree as a prominent based material. According to the result of evaluation, all of these designs are deserved to be made. So, it is concluded that to anticipate the qualified wood as a based material of furniture products, we can use stem waste of sugar palm tree as alternative based material.Pohon aren (Arenga Pinnata) merupakan salah satu sumber daya alam yang potensial digunakan sebagai bahan baku produk mebel. Akan tetapi, potensi batang pohon aren itu belum dimanfaatkan secara maksimal dan hanya terbuang menjadi limbah yang mengotori lingkungan. Di sisi lain, kayu yang selama ini dimanfaatkan sebagai bahan baku produk mebel keberadaannya makin langka dan mahal. Bertolak dari permasalahan itu, penelitian ini bertujuan untuk merancang model-model produk mebel baru dengan memanfaatkan limbah batang pohon sebagai bahan baku utama. Penelitian menggunakan metode eksperimen dengan langkah-langkah: 1) menemukan dan merumuskan konsep-konsep penciptaan desain produk mebel berdasarkan analisis terhadap karakteristik limbah batang pohon aren; 2) mengimplementasikan konsep-konsep yang ditemukan ke dalam bentuk model-model desain produk mebel dari limbah batang pohon aren. Dari hasil penelitian ditemukan konsep â€œtabungâ€ dan konsep ukir tatah sebagai konsep yang tepat untuk diterapkan dalam penciptaan produk-produk mebel dari limbah batang pohon aren. Implementasi dari konsep â€œtabungâ€ dan konsep ukir tatah berhasil dibuat beberapa model desain produk mebel yaitu model meja, model kursi, dan model lemari. Perwujudan desain-desain tersebut telah mempertimbangkan penggunaan limbah batang pohon aren sebagai bahan baku utama. Berdasarkan hasil evaluasi, semua desain tersebut dinyatakan layak untuk diproduksi. Oleh karena itu disimpulkan, bahwa untuk mengantisipasi makin langkanya jenis kayu yang berkualitas sebagai bahan baku produk mebel, dapat digunakan limbah batang-batang pohon aren sebagai bahan baku alternatif.